PENGARUH KOMITE AUDIT, UKURAN PERUSAHAAN, INTENSITAS MODAL, LEVERAGE, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR di BURSA EFEK INDONESIA PERIODE 2016-2022 - Adrian, Muhammad; Anggraini, Nia; Amelia, Sarah; Lussianda, Erfa Okta (Komunitas Manajemen Kompetitif, 2024)
This research aims to examine the impact of several factors on tax avoidance, namely audit committee, company size, capital intensity, leverage, and profitability. This research is quantitative research that uses secondary data and documentary methods. The sample was selected using a purposive sampling technique, by taking 9 food and beverage subsector companies listed on the Indonesia Stock Exchange (BEI) during the 2016-2020 period. Data analysis used multiple linear regression using SPSS version 20. The results showed that company size had a negative influence on tax avoidance, while other factors did not have a significant influence. The limitation of this research is the limited sample size, but this research has the novelty of including 2020 as the observation period. Keywords : audit committee, company size, capital intensity, leverage, profitability, tax avoidance.